MEASURING TRAVEL SATISFACTION AMONG MUSLIM TOURISTS IN MALAYSIA - Mohamed, Muharis; Patwary, Ataul Karim; Abumandil, Mohanad S.S. (South Asian Journal of Social Sciences and Humanities, 2021)
Only limited research has examined the role of religion in a tourism context. This study examines  the travel satisfaction among Muslim tourists in Malaysia. This paper poses the question: What is  the relationship between the Muslim Tourist satisfaction Islamic attributes and revisit intention in  Malaysia? A total of 255 questionnaires consisting of 30 items was distributed to Muslim tourists  in Malaysia through an online survey. Thus, destination marketers should deliver traditional value  to create high customer satisfaction with halal destinations. Marketers should also consider non physical Islamic attributes such as segregation of service delivery when they target consumers with  high religiosity to attract more Muslim tourists.
Keywords: Islamic Tourism; Satisfaction; Malaysia